Kajian Mengenai Dialog Dua Halasebagai Pendekatan Qur’ani dalam Tilawah al-Qur’an: An Anaysis of Two-Way Dialogue as A Quranic Approach in the Recitation of al Qur’an - Abd. Latif, Mohd. Abdul Nasir; Abd. Hadi, Ahmad Zulfiqar Shah; Mohd Yusof, Mohd Yakub @ Zulkifli (Perspektif Jurnal Sains Sosial dan Kemanusiaan, 2014)
A dialogue is a two-way conversation built on three levels; introduction which contains elements of questioning; development which contains elements of argumentation, and an end which contains elements of response such as acceptance or rejection. This article is based on a schematic analysis of Quranic verses that contain dialogues in which the focus is on two-way dialogues. Findings of this study showed many twoway dialogues are found in the long chapters (Surahs) and in the Makkiyah chapters. Thus the dialogues are a Quranic approach which aims at easing the recitation of the Qur’an from the point of view of the physical nature of the verses and the reception level of the reciter. The findings proved that the Qur’an is a mukjizat from Allah SWT and book most read and most frequently read by man.